STUDENTS’ PERCEPTION, CHALLENGES AND OPPORTUNITIES OF USING MINDFULNESS IN ENGLISH WRITING ON THE X PLATFORM - Rara, Milani; Noni, Nurdin; Sakkir, Geminastiti (Universitas Negeri Makassar, 2024)
Focusing on the transformative potential of mindfulness in English writing practice on the X platform, this qualitative study explores how students engage with mindfulness principles in English writing on X. The study involves ten participants and addresses two key research questions: (1) it identifies and analyzes the specific challenges and opportunities associated with integrating mindfulness into writing practices on X on shaping students' writing and engagement and (2) it delves into students' perceptions regarding the incorporation of mindfulness in writing on X compared to traditional writing methods. The results show (1) the significance of integrating mindfulness into writing practices on Twitter, revealing initial skepticism alongside recognition of its potential benefits, and (2) It appears that students perceive similarities and differences between writing mindfulness on X and writing English in the traditional method, students feel differently about how engaged they are and how well they can think deeply.